The BABY BOOM Transcription Factor Activates the LEC1-ABI3-FUS3-LEC2 Network to Induce Somatic Embryogenesis. Issue 2 (22nd August 2017) - Horstman, Anneke; Li, Mengfan; Heidmann, Iris; Weemen, Mieke; Chen, Baojian; Muino, Jose M.; Angenent, Gerco C.; Boutilier, Kim
Abstract : BBM and other AIL transcription factors induce somatic embryogenesis in a dose- and context-dependent mechanism and through direct transcriptional regulation of major embryo identity genes. Abstract: Somatic embryogenesis is an example of induced cellular totipotency, where embryos develop from vegetative cells rather than from gamete fusion. Somatic embryogenesis can be induced in vitro by exposing explants to growth regulators and/or stress treatments. The BABY BOOM (BBM) and LEAFY COTYLEDON1 (LEC1) and LEC2 transcription factors are key regulators of plant cell totipotency, as ectopic overexpression of either transcription factor induces somatic embryo formation from Arabidopsis ( Arabidopsis thaliana ) seedlings without exogenous growth regulators or stress treatments. Although LEC and BBM proteins regulate the same developmental process, it is not known whether they function in the same molecular pathway. We show that BBM transcriptionally regulates LEC1 and LEC2, as well as the two other LAFL genes, FUSCA3 ( FUS3 ) and ABSCISIC ACID   INSENSITIVE3 ( ABI3 ). LEC2 and ABI3 quantitatively regulate BBM-mediated somatic embryogenesis, while FUS3 and LEC1 are essential for this process. BBM-mediated somatic embryogenesis is dose and context dependent, and the context-dependent phenotypes are associated with differential LAFL expression. We also uncover functional redundancy for somatic embryogenesis among other Arabidopsis BBM-like proteins and show that one of these proteins, PLETHORA2, also regulates LAFL gene expression. Our data place BBM upstream of other major regulators of plant embryo identity and totipotency.